Pemberdayaan Masyarakat Melalui Pemanfaatan Lahan Pekarangan Dalam Perspektif Livelihood Di Kabupaten Blitar - Wydha Mustika Maharani; Elsa Febiola (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2023)
The use of empty yards or that has not been used optimally by rural communities who still have a low economy is the basis for the use of yards for planting medicinal family plants, vegetables and various types of flower plants to be able to support the economic needs of the people in Gadungan Village, Gandusari District, Regency Blitar. The purpose of community service is: 1). To find out community empowerment through the utilization of house yards in a livelihood perspective. 2) To determine the impact of empowerment on the welfare of society. The service method used is Active and Participatory Learning. This method is carried out by cultivating vegetable and toga seeds to utilize the yard around the house. This activity consists of self-education and assistance in planting seeds. Periodic monitoring and assistance needs to be done to get maximum results.